Assessing the Development Impact of the Sota Border Post Connecting Indonesia and Papua New Guinea - Nicholas Metherall; Diego Romario De Fretes; Feby Mandibondibo; Talei Caucau (Cenderawasih University, 2022)
Although some studies have mentioned land use and land cover across the borderlands of New Guinea, there have not yet been a series of systematic studies that link the topic with the construction of the Sota border post (Pos Lintas Batas Negara–“PLBN Sota”). With reference to realism, liberalism and asymmetrical power relations, this study examines the development impacts of the Sota border post. A set of interdisciplinary mixed-methods approaches are used including geospatial and earth observation analysis, collation of bureau of statistics data as well as academic and grey literature review. Results provide a baseline land cover assessment for the study area surrounding the Sota border post. There have also been a range of socio-economic and biophysical impacts of the infrastructural and immigration capacities along the Southern borderlands of New Guinea. In terms of international relations, the presence of the Sota border post is expected to foster cooperation between Indonesia and PNG, decrease conflict, and promote stability in the border area. As a result, both realism and liberalism can be used as theoretical frameworks to understand the trajectory of developments along the borderlands. However, due to the asymmetries of power, the rhetoric of liberalism may be rendered less convincing.KEYWORDS:Asymmetries of Power; Indonesia and PNG; International Relations; Land Cover and Land Use Change; Sota Border Post